Selective progesterone receptor modulators: current applications and perspectives. (4th July 2018) - Chabbert-Buffet, N.; Kolanska, K.; Daraï, E.; Bouchard, P.
Abstract: Selective progesterone receptor modulators (SPRMs) are steroid progesterone receptor ligands able to induce agonistic or antagonistic activities. Mifepristone, the class leader, was primarily used for pregnancy termination from the 1980s. Emergency contraception with extended activity was the second major development 30 years later, with mifepristone in some countries and ulipristal acetate world-wide. More recently, ulipristal acetate was released for the treatment of myoma-related uterine bleeding. In addition to a very rapid cessation of bleeding, SPRMs allow a decrease in myoma volume, as do gonadotropin releasing hormone analogs. However, estradiol secretion is not blunted by SPRMs. This offers new alternatives for myoma treatment, especially in women close to menopause. In conclusion, use of SPRMs has allowed significant progress in emergency contraception and treatment of myoma-related symptoms. Numerous future perspectives in women's health care are currently under evaluation.